Helicobacteriosis and coronary heart disease: synthropic pathogenesis - O. N. Pavlov (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To study endoscopic and morphological features of gastric mucosa, oxygen-dependent metabolism of leukocytes and antioxidant potential in patients with varying clinical course of coronary heart disease (CHD).Material and methods. In total, 92 CHD patients and 20 controls without verified CHD diagnosis were examined. All participants underwent fibrogastroesophagoduodenoscopy and the assessment of gastric biopsy morphology, oxygen-dependent leukocyte metabolism, blood antioxidant potential and lipid peroxidation (LPO) activity.Results. Unstable CHD course was often associated with chronic atrophic pangastritis, motoric and microcirculatory disturbances, as well as gastric mucosa erosions. Heavier gastric mucosa invasion with Helicobacter pylori and higher activity of chronic gastritis were linked, regardless of CHD clinical course, to reduced antioxidant potential, activated LPO and increased levels of circulating immune complexes.Conclusion. Heavier gastric mucosa invasion with Helicobacter pylori in patients with unstable CHD clinical course was characterized with higher incidence of repeat coronary events during the next 12 months.